Smoking-induced aggravation of experimental arthritis is dependent of aryl hydrocarbon receptor activation in Th17 cells - Talbot, Jhimmy; Peres, Raphael S.; Pinto, Larissa G.; Oliveira, Rene D. R.; Lima, Kalil A.; Donate, Paula B.; Silva, Jaqueline R.; Ryffel, Bernard; Cunha, Thiago M.; Alves-Filho, José C.; Liew, Foo Y.; Louzada-Junior, Paulo; et al. (Arthritis research & therapy, 2018)
Background Epidemiologic studies have highlighted the association of environmental factors with the development and progression of autoimmune and chronic inflammatory diseases. Among the environmental factors, smoking has been associated with increased susceptibility and poor prognosis in rheumatoid arthritis (RA). However, the immune and molecular mechanism of smoking-induced arthritis aggravation remains unclear. The transcription factor aryl hydrocarbon receptor (AHR) regulates the generation of Th17 cells, CD4 T cells linked the development of autoimmune diseases. AHR is activated by organic compounds including polycyclic aromatic hydrocarbons (PAHs), which are environmental pollutants that are also present in cigarette smoke. In this study, we investigated the role of AHR activation in the aggravation of experiment arthritis induced by exposure to cigarette smoke. Methods Mice were exposed to cigarette smoke during the developmental phase of antigen-induced arthritis and collagen-induced arthritis to evaluate the effects of smoking on disease development. Aggravation of articular inflammation was assessed by measuring neutrophil migration to the joints, increase in articular hyperalgesia and changes in the frequencies of Th17 cells. In vitro studies were performed to evaluate the direct effects of cigarette smoke and PAH on Th17 differentiation. We also used mice genetically deficient for AHR ( Ahr KO) and IL-17Ra ( Il17ra KO) to determine the in vivo mechanism of smoking-induced arthritis aggravation. Results We found that smoking induces arthritis aggravation and increase in the frequencies of Th17 cells. The absence of IL-17 signaling ( Il17ra KO) conferred protection to smoking-induced arthritis aggravation. Moreover, in vitro experiments showed that cigarette smoke can directly increase Th17 differentiation of T cells by inducing AHR activation. Indeed, Ahr KO mice were protected from cigarette smoke-induced arthritis aggravation and did not display increase in TH17 frequencies, suggesting that AHR activation is an important mechanism for cigarette smoke effects on arthritis. Finally, we demonstrate that PAHs are also able to induce arthritis aggravation. Conclusions Our data demonstrate that the disease-exacerbating effects of cigarette smoking are AHR dependent and environmental pollutants with AHR agonist activity can induce arthritis aggravation by directly enhancing Th17 cell development.